Amniotic Sludge and Prematurity: Systematic Review and Meta-analysis - Gabriel Duque Pannain; Ana Maria Gomes Pereira; Maria Luiza Toledo Leite Ferreira da Rocha; Reginaldo Guedes Coelho Lopes (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To perform a systematic review and meta-analysis of studies on maternal, fetal, and neonatal outcomes of women with singleton pregnancies, after spontaneous conception, and with the diagnosis of amniotic sludge before 37 weeks of gestational age. Data Sources We conducted a search on the PubMed, Cochrane, Bireme, and Theses databases until June 2022. Selection of Studies Using the keywords intra-amniotic sludge or fluid sludge or echogenic particles, we found 263 articles, 132 of which were duplicates, and 70 were discarded because they did not meet the inclusion criteria. Data Collection The articles retrieved were analyzed by 2 reviewers; 61 were selected for full-text analysis, 18 were included for a qualitative analysis, and 14, for a quantitative analysis. Data Synthesis Among the maternal outcomes analyzed, there was an increased risk of preterm labor (95% confidence interval [95%CI]: 1.45-2.03), premature rupture of ovular membranes (95%CI: 1.99-3.79), and clinical (95%CI: 1.41-6.19) and histological chorioamnionitis (95%CI: 1.75-3.12). Regarding the fetal outcomes, there was a significant increase in the risk of morbidity (95%CI: 1.80-3.17), mortality (95%CI: 1.14-18.57), admission to the Neonatal Intensive Care Unit (NICU; 95%CI: 1.17-1.95), and neonatal sepsis (95%CI: 2.29-7.55). Conclusion The results of the present study indicate that the presence of amniotic sludge is a risk marker for preterm delivery. Despite the heterogeneity of the studies analyzed, even in patients with other risk factors for prematurity, such as short cervix and previous preterm delivery, the presence of amniotic sludge increases the risk of premature labor. Moreover, antibiotic therapy seems to be a treatment for amniotic sludge, and it may prolong pregnancy.